Distribution and environment-rhodomyrtone of Rhodomyrtus tomentosa in Peninsular Thailand - NUTCHANART KONGCHUAY; JUTARUT IEWKITTAYAKORN; AUNKAMOL KUMNGEN; SUPAYANG P. VORAVUTHIKUNCHAI; SARA BUMRUNGSRI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Kongchuay N, Iewkittayakorn J, Kumngen A, Voravuthikunchai SP, Bumrungsri S. 2026. Distribution and environment-rhodomyrtone relationship of Rhodomyrtus tomentosa in Peninsular Thailand. Biodiversitas 27 (3): d270312. https://doi.org/10.13057/biodiv/d270312. Rhodomyrtus tomentosa is a medicinal plant that yields the antibiotic compound rhodomyrtone. It has been depleted due to changes in land use, therefore, the ecological requirements of the species in its natural habitats need to be investigated to advance its commercial cultivation. This study aimed to explore environmental and soil physicochemical factors affecting the rhodomyrtone content present in R. tomentosa leaves. Soil texture and soil chemical properties were examined. Leaves were extracted and rhodomyrtone content was quantified.  R. tomentosa was found in 54 sites in peninsular Thailand and mostly found in open areas, in acidic soil (pH 4.31-6.36) at low elevation (4-129.5 m asl). The results showed that the species is found in poor soil with very low nitrogen, phosphorus, and potassium contents. R. tomentosa predominantly grows in sandy soil containing fine to coarse sand (125-500 µm). No significant correlation was observed between rhodomyrtone content and soil pH, % organic matter, N, P, or K. In contrast, rhodomyrtone content positively correlates with percent shade cover. Further experimental study is needed to confirm this observation. For commercial cultivation, this shrub should be planted in lowland, sandy, nutrient-poor soil of low pH, and under light shade to promote rhodomyrtone production.